Synthesis and Crystal Structure of RbGdNb6Cl18 - Fakhili Gulo; Saronom Silaban; Christiane Perrin (Departemen Kimia, 2023)
A new quaternary niobium cluster chloride, RbGdNb6Cl18 has been prepared by solid state reaction methods. The RbCl, GdCl3, NbCl5, and niobium powder were mixed in stoichiometric proportions. This mixture was fed into a sealed quartz tube, and heated at 700ºC for 2 days. A single crystal was selected for use in determining the structure of this compound using a single crystal X-ray diffractometer. It crystallizes in the trigonal system, hexagonal setting with space group R-3 (No. 148). The unit cell parameters are: a = 9.3037(2) Å, c = 25.5752(2) Å, V = 1.917.17(7) Å3, and Z =3. The structure consists of discrete cluster units, [Nb6Cl18]4- that separated by Rb+ and Gd3+ cations in a close packed cubic stacking arrangement.